2021
DOI: 10.9734/ijpss/2021/v33i2230685
|View full text |Cite
|
Sign up to set email alerts
|

Nutra-Chemical and Organoleptic Quality Evaluation of Wood Apple (Limonia acidissima L.) Pickle

Abstract: Wood apple is a nutritious minor fruit crop indigenous to India but it is not much popular for the purpose of consumption. The value addition can increase the production and utilization of this valuable fruit crop. Among various value-added products, pickle is popular and traditionally acceptable in India. The present investigation conducted at Department of Horticulture, College of Agriculture, RVSKVV, Gwalior, MP between 2019-20 and 2020-21, to study the nutrients, chemicals and sensory qualities of wood app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The decrease in moisture content is due to the dehydration phenomenon. similar observation were reported by [9,10] found that moisture content of wood apple decreased with storage. [3,10] found that colour and apperance of wood apple decreased with storage.…”
Section: List 1 List Of the Treatment Notions And Their Treatment Com...supporting
confidence: 91%
“…The decrease in moisture content is due to the dehydration phenomenon. similar observation were reported by [9,10] found that moisture content of wood apple decreased with storage. [3,10] found that colour and apperance of wood apple decreased with storage.…”
Section: List 1 List Of the Treatment Notions And Their Treatment Com...supporting
confidence: 91%